EMERGENCY LAW IN THE INDONESIAN LEGAL SYSTEM - Ekowati, Debby (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2022)
This study seeks to determine and examine the position of Emergency Law within the context of Legal Studies and the presence of Emergency Law within the Indonesian Legal System. This study employs a normative legal methodology. The normative legal research approach investigates the law internally, with legal norms as the study object. Government Regulation in Lieu of Law is required if a country is confronted with an urgent and compelling situation that necessitates swift action. For this reason, while issuing Government Regulations in Lieu of Laws, the President implements them by the Constitution, legislative oversight, and, of course, the oversight of the people as sovereigns. The outcomes demonstrated.